Dynamics of coral rubble on reef flats: from individual clast mobilisation to rubble strip morphological change - Aitana Gea-Neuhaus; Tim Scott; Gerd Masselink; Ana Vila-Concejo; Paul S. Kench; Mathilde Lindhart; Floortje E. Roelvink; Tom Hamilton; Ke Lin; Xianfeng Wang (Marine Geology, 2026)

Tidally driven topographic eddies exploited by manta feeding aggregations - Harvey Cairns; Daniel Conley; Christopher Stokes; Tim Scott; Phil Hosegood (Estuarine, Coastal and Shelf Science, 2026)

Building soil organic matter differing in physical fractions for fertilizer nitrogen retention - Quan Tang; Qingde Li; Xiaozhi Wang; Yuanyuan Huang; Tim J. Daniell; Enxuan Wu; Jing Wang; Feiyi Zhang; Zhenwang Li; Scott X. Chang; Zucong Cai; Yves Uwiragiye; et al. (Soil Biology and Biochemistry, 2026)

Sediment characteristics, distribution and pathways on a macro-tidal, energetic and sediment-limited embayed coast - Wassim Seksaf; Tim Scott; Gerd Masselink; Nieves García Valiente; Daniel Conley (Marine Geology, 2026)

The influence of foliage density on the wall surface temperature: An analysis of Hedera helix cultivars - Marie De Groeve; Eda Kale; Anouk De Bock; Scott Allan Orr; Tim De Kock (Urban Climate, 2026)

The Black Array of Broadband Absolute Radiometers Earth Radiation Imager: Science Requirements, Instrument Design, and Concept of Operations - Odele Coddington; Cameron Straatsma; Ginger Drake; Kush Tyagi; Michelle Stephens; Chris Yung; Nathan Tomlin; John Lehman; Chip Bollendonk; Paris Buedel; Katherine Catani; Beth Cervelli; et al. (Advances in Atmospheric Sciences, 2026)
The Black Array of Broadband Absolute Radiometers Earth Radiation Imager (BABAR-ERI) is a small, adaptable nadir-pointed pushbroom imager to measure Earth-leaving broadband radiance from 0.3 µm to 100 µm with higher information content than is currently measured by reducing radiometric uncertainty and enabling cloud-resolving spatial resolution. The three-instrument BABAR-ERI suite fits a 12U CubeSat form factor and contains co-registered science telescope channels for measuring shortwave (0.3 µm to 4.5 µm band) and total radiance (0.3 µm to 100 µm band), dual-channel on-board radiance stability monitors, and a visible-wavelength camera. Novel, 1 × 32 element, electrical-substitution radiometer pixels image the shortwave and total radiance in 1 km × 1 km co-registered ground footprints; longwave radiance (4.5 µm to 100 µm band) is derived from subtraction of the shortwave and total radiance. The dual-channel onboard stability monitors are radiance standard detectors, and their measurements, acquired concurrently with the science telescopes and at much different duty cycles for the dual channels, will be used to track and correct the degradation of the science channels. The single-channel, mid-visible camera facilitates geolocation pointing knowledge and provides scene context information and sub-pixel variability to facilitate measurement stability studies and enable process-level science studies at high spatial resolution. The detectors for the science channels and stability monitors are absolute, ambient-temperature, micro-fabricated, electrical-substitution radiometers with near-perfect optical absorptance across the measurement range from vertically aligned carbon nanotubes. The BABAR-ERI science channels will be characterized over the full measurement range and for variable Earth scenes and deep space temperatures during extensive ground calibrations.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

The Utility of Fish Population Monitoring and Forecast Trigger Development for Designing Adaptive Aquatic Monitoring Plans for Large Industrial Developments - Carolyn JM Brown; Tim J. Arciszewski; R. Allen Curry; D. Scott Smith; Kelly R. Munkittrick (Environmental Management, 2025)

Concurrent invasions of European starlings in Australia and North America reveal population‐specific differentiation in shared genomic regions - Natalie R. Hofmeister; Katarina C. Stuart; Wesley C. Warren; Scott J. Werner; Melissa Bateson; Gregory F. Ball; Katherine L. Buchanan; David W. Burt; Adam P. A. Cardilini; Phillip Cassey; Tim De Meyer; Julia George; et al. (Molecular Ecology, 2025)
A species' success during the invasion of new areas hinges on an interplay between the demographic processes common to invasions and the specific ecological context of the novel environment. Evolutionary genetic studies of invasive species can investigate how genetic bottlenecks and ecological conditions shape genetic variation in invasions, and our study pairs two invasive populations that are hypothesized to be from the same source population to compare how each population evolved during and after introduction. Invasive European starlings ( Sturnus vulgaris ) established populations in both Australia and North America in the 19th century. Here, we compare whole‐genome sequences among native and independently introduced European starling populations to determine how demographic processes interact with rapid evolution to generate similar genetic patterns in these recent and replicated invasions. Demographic models indicate that both invasive populations experienced genetic bottlenecks as expected based on invasion history, and we find that specific genomic regions have differentiated even on this short evolutionary timescale. Despite genetic bottlenecks, we suggest that genetic drift alone cannot explain differentiation in at least two of these regions. The demographic boom intrinsic to many invasions as well as potential inversions may have led to high population‐specific differentiation, although the patterns of genetic variation are also consistent with the hypothesis that this infamous and highly mobile invader adapted to novel selection (e.g., extrinsic factors). We use targeted sampling of replicated invasions to identify and evaluate support for multiple, interacting evolutionary mechanisms that lead to differentiation during the invasion process.

Cross‐Continental Analysis Shows That Disturbance Effects on Reptile Body Condition Do Not Predict Abundance Responses - Kristina J. Macdonald; Don A. Driscoll; Michael D. Craig; Robert A. Davis; Steven J. Hromada; C. M. Gienger; Lee A. Fitzgerald; Daniel J. Leavitt; Danielle K. Walkup; Rickard Abom; Adrian F. Wayne; Gordon R. Friend; et al. (Global Change Biology, 2025)
Ecological disturbances are discrete events that alter or transform the physical, chemical, or biological characteristics of ecosystems. Disturbance can cause animal populations to decline and, according to the risk‐disturbance hypothesis and population collapse framework, these declines can be predicted by declines in animal body condition. However, no research has empirically examined the general relationship between body condition and abundance, nor their relationship in response to disturbance. We used a combined dataset representing 33 studies and > 42,000 observations of 75 species from Australia, New Zealand, Spain and the United States of America to test predictions relating to the relationship between reptile body condition and abundance. We first investigated the relationship at the site level and then used meta‐analytical models to test whether populations showed linked changes in abundance and body condition in response to disturbance. We further tested whether key environmental and species traits influenced this relationship and whether there was a time‐lagged effect of body condition responses on abundance. We found a positive relationship between mean reptile body condition and abundance at the site level. However, the relationship was largely lost when investigating population responses to disturbance. As such, our results provided no support for the risk‐disturbance hypothesis and limited support for the population collapse framework. Therefore, the impacts of disturbance on reptile body condition cannot be assumed to reflect or predict abundance responses. We provide a new conceptual framework that shows how disturbances can modify or uncouple the relationship between abundance and body condition by influencing underlying drivers, such as predation, competition and resource availability. Monitoring programs that infer population impacts based on changes in body condition should first confirm the relationship between these two variables in the relevant study system.

Changes in GEDI-based measures of forest structure after large California wildfires relative to pre-fire conditions - Matthew L. Clark; Christopher R. Hakkenberg; Tim Bailey; Patrick Burns; Scott J. Goetz (Remote Sensing of Environment, 2025)

Pleistocene stratigraphy and sedimentation in the Magadi-Ewaso Nyiro Basins, South Kenya Rift - R. Bernhart Owen; Robin W. Renaut; Tim K. Lowenstein; Mona Stockhecke; Nathan Rabideaux; Kennie Leet; Andrew S. Cohen; Jennifer J. Scott; Veronica Muiruri (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Optimising sub-metre resolution 3D geomorphic change detection over large areas using multitemporal airborne laser scanning with Sentinel-1 InSAR and Sentinel-2 optical observations - Simon J. Walker; Scott N. Wilkinson; Tim R. McVicar; Pascal Castellazzi; Sana Khan (Remote Sensing of Environment, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Measuring the association between the opening of a new multi-national restaurant with young people's eating behaviours - Helen J. Moore; Claire L. O'Malley; Scott Lloyd; Fatemeh Eskandari; Kelly Rose; Mark Butler; Tim G. Townshend; Heather Brown; Daniel Clarkson; Amelia A. Lake (Appetite, 2024)

Drivers of variability in surf zone habitat use by sandy beach fish: Unwitting citizen scientists reveal detailed spatiotemporal patterns - Ryan Hepburn; Tim Scott; Sam Prodger; Benjamin J. Ciotti (Estuarine, Coastal and Shelf Science, 2024)

A review of bites by non-front-fanged snakes (NFFS) of Europe - Giovanni Paolino; Matteo R. Di Nicola; Jean-Marie Ballouard; Xavier Bonnet; Maik Damm; Gaël Le Roux; Tim Lüddecke; Daniele Marini; Scott A. Weinstein; Ignazio Avella (Toxicon, 2024)

Properties of outer solar system pebbles during planetesimal formation from meteor observations - Peter Jenniskens; Paul R. Estrada; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; et al. (Icarus, 2024)

Sediment sorting within a relatively wave-exposed and sandy subtidal seagrass (Zostera marina) meadow - Gerd Masselink; Tom Brown; Tim Scott; Liane Brodie (Marine Geology, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Soil moisture increases stability of North American Pinus species growing in sandy soils - Jeffery B. Cannon; S. Hunter Scully; R. Scott Taylor; Chris J. Peterson; Tim Newson (Forest Ecology and Management, 2024)

Persistence and evidence for accelerated biodegradation of streptomycin in agricultural soils - Megan Demars; Tim McDowell; Justin B. Renaud; Andrew Scott; Michael Fruci; Edward Topp (Science of The Total Environment, 2024)

Lifetime of cm-sized zodiacal dust from the physical and dynamical evolution of meteoroid streams - Peter Jenniskens; Stuart Pilorz; Peter S. Gural; Dave Samuels; Steve Rau; Timothy M.C. Abbott; Jim Albers; Scott Austin; Dan Avner; Jack W. Baggaley; Tim Beck; Solvay Blomquist; et al. (Icarus, 2024)

Corrigendum to “Impacts of environmental feedbacks on the production of a Central Queensland beef enterprise in a future climate” [Agricultural Systems 214 (2024) 1–13/103838] - Duc-Anh An-Vo; David Cobon; Jyoteshna Owens; Adam Liedloff; Tim Cowan; Scott Power (Agricultural Systems, 2024)

Statistical relationships between the Interdecadal Pacific Oscillation and El Niño–Southern Oscillation - Hanna Heidemann; Tim Cowan; Scott B. Power; Benjamin J. Henley (Climate Dynamics, 2024)
The climate of the Pacific Ocean varies on interannual, decadal, and longer timescales. This variability is dominated by the El Niño–Southern Oscillation (ENSO) and the Interdecadal Pacific Oscillation (IPO), both of which have profound impacts on countries within and well beyond the Pacific. To date, previous studies have only examined a small subset of the possible links between ENSO, its diversity, and the IPO. Here we focus on the statistical relationship between decadal variability in ENSO properties and the IPO, testing the null hypothesis that the IPO arises from random decadal changes in ENSO activity, including ENSO diversity. We use observed sea surface temperature (SST) records since 1920 to investigate how the timing, structure, frequency, duration, and magnitude of El Niño and La Niña events differ between IPO phases. We find that using the relative frequency of El Niño and La Niña events and either the mean event duration or SST magnitude can reproduce up to 60% of the IPO Tripole Index timeseries. While the spatial SST patterns that represent the IPO and ENSO are similar, the IPO is meridionally broader in the central to eastern Pacific, which may be caused by a lagged relationship with low-frequency SST variability in the equatorial Pacific. In addition, North Pacific SST anomalies of opposite sign to the tropical Pacific SST anomalies is a unique feature of the IPO that cannot be explained by decadal ENSO variability. This suggests a clear IPO and ENSO relationship, but also independence in some of the IPO’s characteristics.

Microplastic pollution on historic facades: Hidden ‘sink' or urban threat? - Katrin Wilhelm; Sam Woor; Michelle Jackson; Dania Albini; Neil Young; Phani Karamched; Miriam C. Policarpo Wright; Josep Grau-Bove; Scott Allan Orr; Jack Longman; Tim de Kock (Environmental Pollution, 2024)

Impacts of environmental feedbacks on the production of a Central Queensland beef enterprise in a future climate - Duc-Anh An-Vo; David Cobon; Jo Owens; Adam Liedloff; Tim Cowan; Scott Power (Agricultural Systems, 2024)

Organophosphate ester flame retardants and plasticizers in house dust and mental health outcomes among Canadian mothers: A nested prospective cohort study in CHILD - Stephanie A. Foster; Molly L. Kile; Perry Hystad; Miriam L. Diamond; Liisa M. Jantunen; Piush J. Mandhane; Theo J. Moraes; Garthika Navaranjan; James A. Scott; Elinor Simons; Padmaja Subbarao; Tim K. Takaro; et al. (Environmental Research, 2024)

Arc adakitic-like signatures caused by amphibole fractionation: An example from 20 Ma granitoids, Charco Rico district, Panama - Scott Whattam; Carlos Carrasco; Lisard Torró; Hossein Azizi; Youn-Joong Jeong; Sabyasachi Chattopadhyay; Tim Ireland (Lithos, 2023)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Accelerating ocean species discovery and laying the foundations for the future of marine biodiversity research and monitoring - Alex David Rogers; Hannah Appiah-Madson; Jeff A. Ardron; Nicholas J. Bax; Punyasloke Bhadury; Angelika Brandt; Pier-Luigi Buttigieg; Olivier De Clerck; Claudia Delgado; Daniel L. Distel; Adrian Glover; Judith Gobin; et al. (Frontiers in Marine Science, 2023)
Ocean Census is a new Large-Scale Strategic Science Mission aimed at accelerating the discovery and description of marine species. This mission addresses the knowledge gap of the diversity and distribution of marine life whereby of an estimated 1 million to 2 million species of marine life between 75% to 90% remain undescribed to date. Without improved knowledge of marine biodiversity, tackling the decline and eventual extinction of many marine species will not be possible. The marine biota has evolved over 4 billion years and includes many branches of the tree of life that do not exist on land or in freshwater. Understanding what is in the ocean and where it lives is fundamental science, which is required to understand how the ocean works, the direct and indirect benefits it provides to society and how human impacts can be reduced and managed to ensure marine ecosystems remain healthy. We describe a strategy to accelerate the rate of ocean species discovery by: 1) employing consistent standards for digitisation of species data to broaden access to biodiversity knowledge and enabling cybertaxonomy; 2) establishing new working practices and adopting advanced technologies to accelerate taxonomy; 3) building the capacity of stakeholders to undertake taxonomic and biodiversity research and capacity development, especially targeted at low- and middle-income countries (LMICs) so they can better assess and manage life in their waters and contribute to global biodiversity knowledge; and 4) increasing observational coverage on dedicated expeditions. Ocean Census, is conceived as a global open network of scientists anchored by Biodiversity Centres in developed countries and LMICs. Through a collaborative approach, including co-production of science with LMICs, and by working with funding partners, Ocean Census will focus and grow current efforts to discover ocean life globally, and permanently transform our ability to document, describe and safeguard marine species.

Satellite-based shoreline detection along high-energy macrotidal coasts and influence of beach state - Aikaterini Konstantinou; Tim Scott; Gerd Masselink; Kit Stokes; Daniel Conley; Bruno Castelle (Marine Geology, 2023)

Developing an ocean best practice: A case study of marine sampling practices from Australia - Rachel Przeslawski; Neville Barrett; Andrew Carroll; Scott Foster; Brooke Gibbons; Alan Jordan; Jacquomo Monk; Tim Langlois; Ana Lara-Lopez; Jay Pearlman; Kim Picard; Joni Pini-Fitzsimmons; et al. (Frontiers in Marine Science, 2023)
Since 2012, there has been a surge in the numbers of marine science publications that use the term ‘best practice’, yet the term is not often defined, nor is the process behind the best practice development described. Importantly a ‘best practice’ is more than a documented practice that an individual or institution uses and considers good. This article describes a rigorous process to develop an ocean best practice using examples from a case study from Australia in which a suite of nine standard operating procedures were released in 2018 and have since become national best practices. The process to develop a best practice includes three phases 1) scope and recruit, 2) develop and release, 3) revise and ratify. Each phase includes 2-3 steps and associated actions that are supported by the Ocean Best Practices System ( www.oceanbestpractices.org ). The Australian case study differs from many other practices, which only use the second phase (develop and release). In this article, we emphasize the value of the other phases to ensure a practice is truly a ‘best practice’. These phases also have other benefits, including higher uptake of a practice stemming from a sense of shared ownership (from scope and recruit phase) and currency and accuracy (from revise and ratify phase). Although the process described in this paper may be challenging and time-consuming, it optimizes the chance to develop a true best practice that is a) fit-for-purpose with clearly defined scope; b) representative and inclusive of potential users; c) accurate and effective, reflecting emerging technologies and programs; and d) supported and adopted by users.

Vulnerable Waters are Essential to Watershed Resilience - Charles R. Lane; Irena F. Creed; Heather E. Golden; Scott G. Leibowitz; David M. Mushet; Mark C. Rains; Qiusheng Wu; Ellen D’Amico; Laurie C. Alexander; Genevieve A. Ali; Nandita B. Basu; Micah G. Bennett; et al. (Ecosystems, 2023)
Watershed resilience is the ability of a watershed to maintain its characteristic system state while concurrently resisting, adapting to, and reorganizing after hydrological (for example, drought, flooding) or biogeochemical (for example, excessive nutrient) disturbances. Vulnerable waters include non-floodplain wetlands and headwater streams, abundant watershed components representing the most distal extent of the freshwater aquatic network. Vulnerable waters are hydrologically dynamic and biogeochemically reactive aquatic systems, storing, processing, and releasing water and entrained (that is, dissolved and particulate) materials along expanding and contracting aquatic networks. The hydrological and biogeochemical functions emerging from these processes affect the magnitude, frequency, timing, duration, storage, and rate of change of material and energy fluxes among watershed components and to downstream waters, thereby maintaining watershed states and imparting watershed resilience. We present here a conceptual framework for understanding how vulnerable waters confer watershed resilience. We demonstrate how individual and cumulative vulnerable-water modifications (for example, reduced extent, altered connectivity) affect watershed-scale hydrological and biogeochemical disturbance response and recovery, which decreases watershed resilience and can trigger transitions across thresholds to alternative watershed states (for example, states conducive to increased flood frequency or nutrient concentrations). We subsequently describe how resilient watersheds require spatial heterogeneity and temporal variability in hydrological and biogeochemical interactions between terrestrial systems and down-gradient waters, which necessitates attention to the conservation and restoration of vulnerable waters and their downstream connectivity gradients. To conclude, we provide actionable principles for resilient watersheds and articulate research needs to further watershed resilience science and vulnerable-water management.

An Interlaboratory Study to Identify Potential Visible Protein-Like Particle Standards - Srivalli N. Telikepalli; Michael J. Carrier; Dean C. Ripple; Greg Barnett; Ashwinkumar Bhirde; Donna Bolton; George M. Bou-Assaf; Erica Ferrari; Scott Leigh; Sophia Levitskaya-Seaman; Tim Menzen; Felix Nikels; et al. (AAPS PharmSciTech, 2022)
Visible protein-like particle standards may improve visual inspection and/or appearance testing practices used in the biotechnology industry. They may improve assay performance resulting in better alignment and more standardized training among different companies. The National Institute of Standards and Technology (NIST) has conducted an interlaboratory study to test whether the standards under development mimic typical proteinaceous particles found in biotherapeutics and if they can be implemented during the visual inspection process. Fourteen organizations from industry and government have participated. A total of 20 labs from these 14 organizations participated with analysts from 6 formulation, 7 analytical, 4 quality control, and 3 manufacturing labs. The circulated samples consisted of abraded ethylene tetrafluoroethylene (ETFE) particles or photolithographic particles. The results consist of qualitative ratings, which varied substantially among organizations and within labs. Polydisperse ETFE particle suspensions, containing particles enriched in greater than 150 µm in size, were rated more favorably than the photolithographic particles by formulation and analytical scientists. The largest monodisperse photolithographic particles (approximately 300 µm in size) were favored equally compared to ETFE by all scientists. Solution modifications to decrease the settling rate or to alter optical properties of the ETFE solutions yielded lower ratings by the analysts. Both particle types received mixed ratings for their usability and for their application for visual inspection and for training purposes. Industry feedback will assist NIST in developing reference material(s) for visible protein-like particles. Graphical Abstract

Extinction risk of the endemic vascular flora of Kauai, Hawaii, based on IUCN assessments - Nina Rønsted; Seana K. Walsh; Margaret Clark; Merlin Edmonds; Tim Flynn; Scott Heintzman; Alexander Loomis; David Lorence; Uma Nagendra; Ben Nyberg; Michael Opgenorth; Lauren Weisenberger; et al. (Conservation Biology, 2022)
The International Union for Conservation of Nature's Red List of Threatened Species (IUCN Red List) is the world's most comprehensive information source on the global conservation status of species. Governmental agencies and conservation organizations increasingly rely on IUCN Red List assessments to develop conservation policies and priorities. Funding agencies use the assessments as evaluation criteria, and researchers use meta‐analysis of red‐list data to address fundamental and applied conservation science questions. However, the circa 143,000 IUCN assessments represent a fraction of the world's biodiversity and are biased in regional and organismal coverage. These biases may affect conservation priorities, funding, and uses of these data to understand global patterns. Isolated oceanic islands are characterized by high endemicity, but the unique biodiversity of many islands is experiencing high extinction rates. The archipelago of Hawaii has one of the highest levels of endemism of any floristic region; 90% of its 1367 native vascular plant taxa are classified as endemic. We used the IUCN's assessment of the complete single‐island endemic (SIE) vascular plant flora of Kauai, Hawaii, to assess the proportion and drivers of decline of threatened plants in an oceanic island setting. We compared the IUCN assessments with federal, state, and other local assessments of Kauai species or taxa of conservation concern. Finally, we conducted a preliminary assessment for all 1044 native vascular plants of Hawaii based on IUCN criterion B by estimating area of occupancy, extent of occurrence, and number of locations to determine whether the pattern found for the SIE vascular flora of Kauai is comparable to the native vascular flora of the Hawaiian Islands. We compared our results with patterns observed for assessments of other floras. According to IUCN, 256 SIE vascular plant taxa are threatened with extinction and 5% are already extinct. This is the highest extinction risk reported for any flora to date. The preliminary assessment of the native vascular flora of Hawaii showed that 72% (753 taxa) is threatened. The flora of Hawaii may be one of the world's most threatened; thus, increased and novel conservation measures in the state and on other remote oceanic islands are urgently needed.

How should we judge edible oils and fats? An umbrella review of the health effects of nutrient and bioactive components found in edible oils and fats - Scott B. Teasdale; Skye Marshall; Kylie Abbott; Tim Cassettari; Emily Duve; Flavia Fayet-Moore (Critical Reviews in Food Science and Nutrition, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Persistent thermally driven shift in the functional trait structure of herbivorous fishes: Evidence of top‐down control on the rebound potential of temperate seaweed forests? - Nestor E. Bosch; Matthew McLean; Salvador Zarco‐Perello; Scott Bennett; Rick D. Stuart‐Smith; Adriana Vergés; Albert Pessarrodona; Fernando Tuya; Tim Langlois; Claude Spencer; Sahira Bell; Benjamin J. Saunders; et al. (Global Change Biology, 2022)
Extreme climatic events can reshape the functional structure of ecological communities, potentially altering ecological interactions and ecosystem functioning. While these shifts have been widely documented, evidence of their persistence and potential flow‐on effects on ecosystem structure following relaxation of extreme events remains limited. Here, we investigate changes in the functional trait structure – encompassing dimensions of resource use, thermal affinity, and body size – of herbivorous fishes in a temperate reef system that experienced an extreme marine heatwave (MHW) and subsequent return to cool conditions. We quantify how changes in the trait structure modified the nature and intensity of herbivory‐related functions (macroalgae, turf, and sediment removal), and explored the potential flow‐on effects on the recovery dynamics of macroalgal foundation species. The trait structure of the herbivorous fish assemblage shifted as a result of the MHW, from dominance of cool‐water browsing species to increased evenness in the distribution of abundance among temperate and tropical guilds supporting novel herbivory roles (i.e. scraping, cropping, and sediment sucking). Despite the abundance of tropical herbivorous fishes and intensity of herbivory‐related functions declined following a period of cooling after the MHW, the underlying trait structure displayed limited recovery. Concomitantly, algal assemblages displayed a lack of recovery of the formerly dominant foundational species, the kelp Ecklonia radiata , transitioning to an alternative state dominated by turf and Sargassum spp. Our study demonstrates a legacy effect of an extreme MHW and exemplified the value of monitoring phenotypic (trait mediated) changes in the nature of core ecosystem processes to predict and adapt to the future configurations of changing reef ecosystems.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Runs of homozygosity in killer whale genomes provide a global record of demographic histories - Andrew D. Foote; Rebecca Hooper; Alana Alexander; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; Tim Collins; Rochelle Constantine; Luciano Dalla Rosa; Nicholas J. Davison; et al. (Molecular Ecology, 2021)
Runs of homozygosity (ROH) occur when offspring inherit haplotypes that are identical by descent from each parent. Length distributions of ROH are informative about population history; specifically, the probability of inbreeding mediated by mating system and/or population demography. Here, we investigated whether variation in killer whale ( Orcinus orca ) demographic history is reflected in genome‐wide heterozygosity and ROH length distributions, using a global data set of 26 genomes representative of geographic and ecotypic variation in this species, and two F1 admixed individuals with Pacific‐Atlantic parentage. We first reconstructed demographic history for each population as changes in effective population size through time using the pairwise sequential Markovian coalescent (PSMC) method. We found a subset of populations declined in effective population size during the Late Pleistocene, while others had more stable demography. Genomes inferred to have undergone ancestral declines in effective population size, were autozygous at hundreds of short ROH ( 1.5 Mb) were found in low latitude populations, and populations of known conservation concern. These include a Scottish killer whale, for which 37.8% of the autosomes were comprised of ROH >1.5 Mb in length. The fate of this population, in which only two adult males have been sighted in the past five years, and zero fecundity over the last two decades, may be inextricably linked to its demographic history and consequential inbreeding depression.

Stability of tropical forest tree carbon‐water relations in a rainfall exclusion treatment through shifts in effective water uptake depth - Alexandria L. Pivovaroff; Nate G. McDowell; Tayana Barrozo Rodrigues; Tim Brodribb; Lucas A. Cernusak; Brendan Choat; Charlotte Grossiord; Yoko Ishida; Kolby J. Jardine; Susan Laurance; Riley Leff; Weibin Li; et al. (Global Change Biology, 2021)
Increasing severity and frequency of drought is predicted for large portions of the terrestrial biosphere, with major impacts already documented in wet tropical forests. Using a 4‐year rainfall exclusion experiment in the Daintree Rainforest in northeast Australia, we examined canopy tree responses to reduced precipitation and soil water availability by quantifying seasonal changes in plant hydraulic and carbon traits for 11 tree species between control and drought treatments. Even with reduced soil volumetric water content in the upper 1 m of soil in the drought treatment, we found no significant difference between treatments for predawn and midday leaf water potential, photosynthesis, stomatal conductance, foliar stable carbon isotope composition, leaf mass per area, turgor loss point, xylem vessel anatomy, or leaf and stem nonstructural carbohydrates. While empirical measurements of aboveground traits revealed homeostatic maintenance of plant water status and traits in response to reduced soil moisture, modeled belowground dynamics revealed that trees in the drought treatment shifted the depth from which water was acquired to deeper soil layers. These findings reveal that belowground acclimation of tree water uptake depth may buffer tropical rainforests from more severe droughts that may arise in future with climate change.

Boat-electrofishing transect location and flow levels: influence on riverine fish monitoring in non-wadeable habitats - Scott M. Reid; Tim Haxton; Lee F. G. Gutowsky (Environmental Monitoring and Assessment, 2021)

An LCA of hospital pathology testing - Scott McAlister; Tim Grant; Forbes McGain (The International Journal of Life Cycle Assessment, 2021)

Human small intestinal organotypic culture model for drug permeation, inflammation, and toxicity assays - Jan Markus; Tim Landry; Zachary Stevens; Hailey Scott; Pierre Llanos; Michelle Debatis; Alexander Armento; Mitchell Klausner; Seyoum Ayehunie (In Vitro Cellular & Developmental Biology - Animal, 2021)

What We Do in the Shallows: Natural and Anthropogenic Seafloor Geomorphologies in a Drowned River Valley, New Zealand - Sally J. Watson; Helen Neil; Marta Ribó; Geoffroy Lamarche; Lorna J. Strachan; Kevin MacKay; Steve Wilcox; Tim Kane; Alan Orpin; Scott Nodder; Arne Pallentin; Tilmann Steinmetz (Frontiers in Marine Science, 2020)

The COVID-19 pandemic: local to global implications as perceived by urban ecologists - Ian Douglas; Mark Champion; Joy Clancy; David Haley; Marcelo Lopes de Souza; Kerry Morrison; Alan Scott; Richard Scott; Miriam Stark; Joanne Tippett; Piotr Tryjanowski; Tim Webb (Socio-Ecological Practice Research, 2020)
The global COVID-19 pandemic is affecting everyone, but in many different ways, stimulating contrasting reactions and responses: opportunities for some, difficulties for many. A simple survey of how individual workers in urban ecology have been coping with COVID-19 constraints found divergent responses to COVID-19 on people’s activities, both within countries and between continents. Many academics felt frustrated at being unable to do fieldwork, but several saw opportunities to change ways of working and review their engagement with the natural world. Some engaging with social groups found new ways of sharing ideas and developing aspirations without face-to-face contact. Practitioners creating and managing urban greenspaces had to devise ways to work and travel while maintaining social distancing. Many feared severe funding impacts from changed local government priorities. Around the world, the COVID-19 pandemic has amplified issues, such as environmental injustice, disaster preparation and food security, that have been endemic in most countries across the global south in modern times. However, developing and sustaining the strong community spirit shown in many places will speed economic recovery and make cities more resilient against future geophysical and people-made disasters. Significantly, top-down responses and one-size-fits-all solutions, however good the modelling on which they are based, are unlikely to succeed without the insights that local knowledge and community understanding can bring. We all will have to look at disaster preparation in a more comprehensive, caring and consistent way in future.

Seasonal Predictions of Shoreline Change, Informed by Climate Indices - Dan Hilton; Mark Davidson; Tim Scott (Journal of Marine Science and Engineering, 2020)
With sea level rise accelerating and coastal populations increasing, the requirement of coastal managers and scientists to produce accurate predictions of shoreline change is becoming ever more urgent. Waves are the primary driver of coastal evolution, and much of the interannual variability of the wave conditions in the Northeast Atlantic can be explained by broadscale patterns in atmospheric circulation. Two of the dominant climate indices that capture the wave climate in western Europe’s coastal regions are the ‘Western Europe Pressure Anomaly’ (WEPA) and ‘North Atlantic Oscillation’ (NAO). This study utilises a shoreline prediction model (ShoreFor) which is forced by synthetic waves to investigate whether forecasts can be improved when the synthetic wave generation algorithm is informed by relevant climate indices. The climate index-informed predictions were tested against a baseline case where no climate indices were considered over eight winter periods at Perranporth, UK. A simple adaption to the synthetic wave-generating process has allowed for monthly climate index values to be considered before producing the 103 random waves used to force the model. The results show that improved seasonal predictions of shoreline change are possible if climate indices are known a priori. For NAO, modest gains were made over the uninformed ShoreFor model, with a reduction in average root mean square error (RMSE) of 7% but an unchanged skill score. For WEPA, the gains were more significant, with the average RMSE 12% lower and skill score 5% higher. Highlighted is the importance of selecting an appropriate index for the site location. This work suggests that better forecasts of shoreline change could be gained from consideration of a priori knowledge of climatic indices in the generation of synthetic waves.

Coastal Harmful Algae Bloom Monitoring via a Sustainable, Sail-Powered Mobile Platform - Jordon S. Beckler; Ethan Arutunian; Tim Moore; Bob Currier; Eric Milbrandt; Scott Duncan (Frontiers in Marine Science, 2019)

Future Ocean Observations to Connect Climate, Fisheries and Marine Ecosystems - Jörn O. Schmidt; Steven J. Bograd; Haritz Arrizabalaga; José L. Azevedo; Steven J. Barbeaux; John A. Barth; Tim Boyer; Stephanie Brodie; Juan José Cárdenas; Scott Cross; Jean-Noël Druon; Agneta Fransson; et al. (Frontiers in Marine Science, 2019)

Killer whale genomes reveal a complex history of recurrent admixture and vicariance - Andrew D. Foote; Michael D. Martin; Marie Louis; George Pacheco; Kelly M. Robertson; Mikkel‐Holger S. Sinding; Ana R. Amaral; Robin W. Baird; Charles Scott Baker; Lisa Ballance; Jay Barlow; Andrew Brownlow; et al. (Molecular Ecology, 2019)
Reconstruction of the demographic and evolutionary history of populations assuming a consensus tree‐like relationship can mask more complex scenarios, which are prevalent in nature. An emerging genomic toolset, which has been most comprehensively harnessed in the reconstruction of human evolutionary history, enables molecular ecologists to elucidate complex population histories. Killer whales have limited extrinsic barriers to dispersal and have radiated globally, and are therefore a good candidate model for the application of such tools. Here, we analyse a global data set of killer whale genomes in a rare attempt to elucidate global population structure in a nonhuman species. We identify a pattern of genetic homogenisation at lower latitudes and the greatest differentiation at high latitudes, even between currently sympatric lineages. The processes underlying the major axis of structure include high drift at the edge of species' range, likely associated with founder effects and allelic surfing during postglacial range expansion. Divergence between Antarctic and non‐Antarctic lineages is further driven by ancestry segments with up to four‐fold older coalescence time than the genome‐wide average; relicts of a previous vicariance during an earlier glacial cycle. Our study further underpins that episodic gene flow is ubiquitous in natural populations, and can occur across great distances and after substantial periods of isolation between populations. Thus, understanding the evolutionary history of a species requires comprehensive geographic sampling and genome‐wide data to sample the variation in ancestry within individuals.

Regionally-Coherent Embayment Rotation: Behavioural Response to Bi-Directional Waves and Atmospheric Forcing - Mark Wiggins; Tim Scott; Gerd Masselink; Paul Russell; Nieves G. Valiente (Journal of Marine Science and Engineering, 2019)
Bi-directional wave climates often drive beach rotation, increasing erosional risk at semi-sheltered locations. Identification of rotation and forcing mechanisms is vital to future coastal defence. In this study, regional investigation of modelled wave data revealed strong bi-directionality between dominant south-westerly and sub-dominant easterly waves for 14 offshore locations along the length of the south coast of England, U.K. South-westerly wave power was well correlated to positive phases of the West Europe Pressure Anomaly (WEPA), whilst easterly wave power was well correlated with negative phases of the North Atlantic Oscillation (NAO). Additionally, decadal records of beach morphological change and associated wave forcing, were investigated for 22 coastal sites across the same region. Significant rotational behaviour was identified at 11 sites, leading to the creation of a rotation index. Beach rotation was attributed to shoreline angle, with the strongest rotation occurring at south-east-facing beaches, with high obliquity to dominant south-westerly waves. The beach rotation index was well correlated with the normalized balance of wave power from opposing south-westerly and easterly directions. Direct correlations between beach rotation and WEPA at two sites showed that future forecasts of atmospheric indices may allow prediction of rotational beach state, at seasonal scales.

A Suite of Field Manuals for Marine Sampling to Monitor Australian Waters - Rachel Przeslawski; Scott Foster; Jacquomo Monk; Neville Barrett; Phil Bouchet; Andrew Carroll; Tim Langlois; Vanessa Lucieer; Joel Williams; Nicholas Bax (Frontiers in Marine Science, 2019)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Surf zone hazards and injuries on beaches in SW France - Bruno Castelle; Rob Brander; Eric Tellier; Bruno Simonnet; Tim Scott; Jak McCarroll; Jean-Michel Campagne; Thibault Cavailhes; Pierre Lechevrel (Natural Hazards, 2018)

Wave and Tidal Controls on Embayment Circulation and Headland Bypassing for an Exposed, Macrotidal Site - R. Jak McCarroll; Gerd Masselink; Nieves G. Valiente; Tim Scott; Erin V. King; Daniel Conley (Journal of Marine Science and Engineering, 2018)
Headland bypassing is the transport of sediment around rocky headlands by wave and tidal action, associated with high-energy conditions and embayment circulation (e.g., mega-rips). Bypassing may be a key component in the sediment budget of many coastal cells, the quantification of which is required to predict the coastal response to extreme events and future coastal change. Waves, currents, and water levels were measured off the headland of a sandy, exposed, and macrotidal beach in 18-m and 26-m depths for 2 months. The observations were used to validate a Delft3D morphodynamic model, which was subsequently run for a wide range of scenarios. Three modes of bypassing were determined: (i) tidally-dominated control during low–moderate wave conditions [flux O (0–102 m3 day−1)]; (ii) combined tidal- and embayment circulation controls during moderate–high waves [O (103 m3 day−1)]; and (iii) multi-embayment circulation control during extreme waves [O (104 m3 day−1)]. A site-specific bypass parameter is introduced, which accurately (R2 = 0.95) matches the modelled bypass rates. A 5-year hindcast predicts bypassing is an order of magnitude less than observed cross-shore fluxes during extreme events, suggesting that bypassing at this site is insignificant at annual timescales. This work serves a starting point to generalise the prediction of headland bypassing.

Genetic distinctiveness of brown pelicans (Pelecanus occidentalis) from the Galápagos Islands compared to continental North America - Scott A. Taylor; Melissa Jenkins; Meera Manghani; Tim Birt; David J. Anderson; Gustavo Jiménez-Uzcátegui; Vicki Friesen (Conservation Genetics, 2018)

Acute liver effects, disposition and metabolic fate of [14C]-fenclozic acid following oral administration to normal and bile-cannulated male C57BL/6J mice - Kathryn Pickup; Scott Martin; Elizabeth A. Partridge; Huw B. Jones; Jonathan Wills; Tim Schulz-Utermoehl; Alan McCarthy; Alison Rodrigues; Chris Page; Kerry Ratcliffe; Sunil Sarda; Ian D. Wilson (Archives of Toxicology, 2017)

Current and projected global distribution of Phytophthora cinnamomi , one of the world's worst plant pathogens - Treena I. Burgess; John K. Scott; Keith L. Mcdougall; Michael J. C. Stukely; Colin Crane; William A. Dunstan; Frances Brigg; Vera Andjic; Diane White; Tim Rudman; Frans Arentz; Noboru Ota; et al. (Global Change Biology, 2017)
Globally, Phytophthora cinnamomi is listed as one of the 100 worst invasive alien species and active management is required to reduce impact and prevent spread in both horticulture and natural ecosystems. Conversely, there are regions thought to be suitable for the pathogen where no disease is observed. We developed a climex model for the global distribution of P. cinnamomi based on the pathogen's response to temperature and moisture and by incorporating extensive empirical evidence on the presence and absence of the pathogen. The climex model captured areas of climatic suitability where P. cinnamomi occurs that is congruent with all available records. The model was validated by the collection of soil samples from asymptomatic vegetation in areas projected to be suitable by the model for which there were few records. DNA was extracted, and the presence or absence of P. cinnamomi was determined by high‐throughput sequencing ( HTS ). While not detected using traditional isolation methods, HTS detected P. cinnamomi at higher elevations in eastern Australia and central Tasmania as projected by the climex model. Further support for the climex model was obtained using the large data set from south‐west Australia where the proportion of positive records in an area is related to the Ecoclimatic Index value for the same area. We provide for the first time a comprehensive global map of the current P. cinnamomi distribution, an improved climex model of the distribution, and a projection to 2080 of the distribution with predicted climate change. This information provides the basis for more detailed regional‐scale modelling and supports risk assessment for governments to plan management of this important soil‐borne plant pathogen.

Strategies to enable the adoption of animal biotechnology to sustainably improve global food safety and security - Mark Tizard; Eric Hallerman; Scott Fahrenkrug; Martina Newell-McGloughlin; John Gibson; Frans de Loos; Stefan Wagner; Götz Laible; Jae Yong Han; Michael D’Occhio; Lisa Kelly; John Lowenthal; et al. (Transgenic Research, 2016)

Characterisation of the clinical and activated T cell response to repeat delayed-type hypersensitivity skin challenges in human subjects, with KLH and PPD, as a potential model to test T cell-targeted therapies - Alexandra Belson; Tim Schmidt; Disala Fernando; Kelly Hardes; Nicola Scott; Sara Brett; Deborah Clark; João Joaquim Oliveira; Bill Davis; Simon McHugh; John Stone (Inflammation Research, 2016)

Targeted demersal fish species exhibit variable responses to long-term protection from fishing at the Houtman Abrolhos Islands - Katrina R. Bornt; Dianne L. McLean; Tim J. Langlois; Euan S. Harvey; Lynda M. Bellchambers; Scott N. Evans; Stephen J. Newman (Coral Reefs, 2015)

Impacts of eucalypt plantation management on soil faunal communities and nutrient bioavailability: trading function for dependence? - Tiffany J. Aslam; Tim G. Benton; Uffe N. Nielsen; Scott N. Johnson (Biology and Fertility of Soils, 2015)

Genome edited sheep and cattle - Chris Proudfoot; Daniel F. Carlson; Rachel Huddart; Charles R. Long; Jane H. Pryor; Tim J. King; Simon G. Lillico; Alan J. Mileham; David G. McLaren; C. Bruce A. Whitelaw; Scott C. Fahrenkrug (Transgenic Research, 2015)

Obesity and head and neck cancer risk and survival by human papillomavirus serology - Xinmiao Tan; Heather H. Nelson; Scott M. Langevin; Michael McClean; Carmen J. Marsit; Tim Waterboer; Michael Pawlita; Karl T. Kelsey; Dominique S. Michaud (Cancer Causes & Control, 2015)

Closed-Loop Brain–Machine–Body Interfaces for Noninvasive Rehabilitation of Movement Disorders - Frédéric D. Broccard; Tim Mullen; Yu Mike Chi; David Peterson; John R. Iversen; Mike Arnold; Kenneth Kreutz-Delgado; Tzyy-Ping Jung; Scott Makeig; Howard Poizner; Terrence Sejnowski; Gert Cauwenberghs (Annals of Biomedical Engineering, 2014)

Comparison of Dilute Acid and Sulfite Pretreatment for Enzymatic Saccharification of Earlywood and Latewood of Douglas fir - Chao Zhang; Xiaochun Lei; C. Tim Scott; J.Y. Zhu; Kecheng Li (BioEnergy Research, 2014)

Virus species polemics: 14 senior virologists oppose a proposed change to the ICTV definition of virus species - Marc H. V. Van Regenmortel; Hans-Wolfgang Ackermann; Charles H. Calisher; Ralf G. Dietzgen; Marian C. Horzinek; Gunther M. Keil; Brian W. J. Mahy; Giovanni P. Martelli; Frederick A. Murphy; Craig Pringle; Bert K. Rima; Tim Skern; et al. (Archives of Virology, 2013)

Whole farm analysis of automatic section control for agricultural machinery - Jordan Shockley; Carl R. Dillon; Tim Stombaugh; Scott Shearer (Precision Agriculture, 2012)

Cryptic introgression between murre sister species (Uria spp.) in the Pacific low Arctic: frequency, cause, and implications - Scott A. Taylor; Anoma Patirana; Tim Birt; Vicki Friesen (Polar Biology, 2012)

Modelled and measured concentrations of peroxy radicals and nitrate radical in the U.S. Gulf Coast region during TexAQS 2006 - Roberto Sommariva; Tim S. Bates; Daniel Bon; Daniel M. Brookes; Joost A. de Gouw; Jessica B. Gilman; Scott C. Herndon; William C. Kuster; Brian M. Lerner; Paul S. Monks; Hans D. Osthoff; Alex E. Parker; et al. (Journal of Atmospheric Chemistry, 2011)

Advancing objectives-based, integrated ocean management through marine spatial planning: current and future directions on the Scotian Shelf off Nova Scotia, Canada - Tim Hall; Melanie MacLean; Scott Coffen-Smout; Glen Herbert (Journal of Coastal Conservation, 2011)

Generation of Priority Research Questions to Inform Conservation Policy and Management at a National Level - MURRAY A. RUDD; KAREN F. BEAZLEY; STEVEN J. COOKE; ERICA FLEISHMAN; DANIEL E. LANE; MICHAEL B. MASCIA; ROBIN ROTH; GARY TABOR; JISELLE A. BAKKER; TERESA BELLEFONTAINE; DOMINIQUE BERTEAUX; BERNARD CANTIN; et al. (Conservation Biology, 2011)
Integrating knowledge from across the natural and social sciences is necessary to effectively address societal tradeoffs between human use of biological diversity and its preservation. Collaborative processes can change the ways decision makers think about scientific evidence, enhance levels of mutual trust and credibility, and advance the conservation policy discourse. Canada has responsibility for a large fraction of some major ecosystems, such as boreal forests, Arctic tundra, wetlands, and temperate and Arctic oceans. Stressors to biological diversity within these ecosystems arise from activities of the country's resource‐based economy, as well as external drivers of environmental change. Effective management is complicated by incongruence between ecological and political boundaries and conflicting perspectives on social and economic goals. Many knowledge gaps about stressors and their management might be reduced through targeted, timely research. We identify 40 questions that, if addressed or answered, would advance research that has a high probability of supporting development of effective policies and management strategies for species, ecosystems, and ecological processes in Canada. A total of 396 candidate questions drawn from natural and social science disciplines were contributed by individuals with diverse organizational affiliations. These were collaboratively winnowed to 40 by our team of collaborators. The questions emphasize understanding ecosystems, the effects and mitigation of climate change, coordinating governance and management efforts across multiple jurisdictions, and examining relations between conservation policy and the social and economic well‐being of Aboriginal peoples. The questions we identified provide potential links between evidence from the conservation sciences and formulation of policies for conservation and resource management. Our collaborative process of communication and engagement between scientists and decision makers for generating and prioritizing research questions at a national level could be a model for similar efforts beyond Canada.

Indigenous culture and adaptation to climate change: sockeye salmon and the St’át’imc people - Colleen Jacob; Tim McDaniels; Scott Hinch (Mitigation and Adaptation Strategies for Global Change, 2010)

Polymorphic microsatellite loci for the threatened Xantus’s Murrelet (Synthliboramphus hypoleucus scrippsi) - Tim P. Birt; Zhengxin Sun; Harry R. Carter; Darrell L. Whitworth; Scott H. Newman; Vicki L. Friesen (Conservation Genetics Resources, 2010)

Trophic level asynchrony in rates of phenological change for marine, freshwater and terrestrial environments - STEPHEN J. THACKERAY; TIMOTHY H. SPARKS; MORTEN FREDERIKSEN; SARAH BURTHE; PHILIP J. BACON; JAMES R. BELL; MARC S. BOTHAM; TOM M. BRERETON; PAUL W. BRIGHT; LAURENCE CARVALHO; TIM CLUTTON‐BROCK; ALISTAIR DAWSON; et al. (Global Change Biology, 2010)
Recent changes in the seasonal timing (phenology) of familiar biological events have been one of the most conspicuous signs of climate change. However, the lack of a standardized approach to analysing change has hampered assessment of consistency in such changes among different taxa and trophic levels and across freshwater, terrestrial and marine environments. We present a standardized assessment of 25 532 rates of phenological change for 726 UK terrestrial, freshwater and marine taxa. The majority of spring and summer events have advanced, and more rapidly than previously documented. Such consistency is indicative of shared large scale drivers. Furthermore, average rates of change have accelerated in a way that is consistent with observed warming trends. Less coherent patterns in some groups of organisms point to the agency of more local scale processes and multiple drivers. For the first time we show a broad scale signal of differential phenological change among trophic levels; across environments advances in timing were slowest for secondary consumers, thus heightening the potential risk of temporal mismatch in key trophic interactions. If current patterns and rates of phenological change are indicative of future trends, future climate warming may exacerbate trophic mismatching, further disrupting the functioning, persistence and resilience of many ecosystems and having a major impact on ecosystem services.

A proposal to change existing virus species names to non-Latinized binomials - Marc H. V. Van Regenmortel; Donald S. Burke; Charles H. Calisher; Ralf G. Dietzgen; Claude M. Fauquet; Said A. Ghabrial; Peter B. Jahrling; Karl M. Johnson; Michael R. Holbrook; Marian C. Horzinek; Günther M. Keil; Jens H. Kuhn; et al. (Archives of Virology, 2010)

Range‐wide distribution of genetic diversity in the North American tree Juglans cinerea : a product of range shifts, not ecological marginality or recent population decline - SEAN M. HOBAN; DANIEL S. BORKOWSKI; SUNSHINE L. BROSI; TIM S. McCLEARY; LAURA M. THOMPSON; JASON S. McLACHLAN; MARIE A. PEREIRA; SCOTT E. SCHLARBAUM; JEANNE ROMERO‐SEVERSON (Molecular Ecology, 2010)
The spatial distribution of genetic diversity is a product of recent and historical ecological processes, as well as anthropogenic activities. A current challenge in population and conservation genetics is to disentangle the relative effects of these processes, as a first step in predicting population response to future environmental change. In this investigation, we compare the influence of contemporary population decline, contemporary ecological marginality and postglacial range shifts. Using classical model comparison procedures and Bayesian methods, we have identified postglacial range shift as the clear determinant of genetic diversity, differentiation and bottlenecks in 29 populations of butternut, Juglans cinerea L., a North American outcrossing forest tree. Although butternut has experienced dramatic 20th century decline because of an introduced fungal pathogen, our analysis indicates that recent population decline has had less genetic impact than postglacial recolonization history. Location within the range edge vs. the range core also failed to account for the observed patterns of diversity and differentiation. Our results suggest that the genetic impact of large‐scale recent population losses in forest trees should be considered in the light of Pleistocene‐era large‐scale range shifts that may have had long‐term genetic consequences. The data also suggest that the population dynamics and life history of wind‐pollinated forest trees may provide a buffer against steep population declines of short duration, a result having important implications for habitat management efforts, ex situ conservation sampling and population viability analysis.

Long-Term Trends in Submersed Aquatic Vegetation (SAV) in Chesapeake Bay, USA, Related to Water Quality - Robert J. Orth; Michael R. Williams; Scott R. Marion; David J. Wilcox; Tim J. B. Carruthers; Kenneth A. Moore; W. Michael Kemp; William C. Dennison; Nancy Rybicki; Peter Bergstrom; Richard A. Batiuk (Estuaries and Coasts, 2010)

A Serial Analysis of Gene Expression Profile of the Alzheimer’s Disease Tg2576 Mouse Model - Amee J. George; Lavinia Gordon; Tim Beissbarth; Irene Koukoulas; R. M. Damian Holsinger; Victoria Perreau; Roberto Cappai; Seong-Seng Tan; Colin L. Masters; Hamish S. Scott; Qiao-Xin Li (Neurotoxicity Research, 2010)

SAGE Analysis of Genes Differentially Expressed in Presymptomatic TgSOD1G93A Transgenic Mice Identified Cellular Processes Involved in Early Stage of ALS Pathology - Michel Guipponi; Qiao-Xin Li; Lavinia Hyde; Tim Beissbarth; Gordon K. Smyth; Colin L. Masters; Hamish S. Scott (Journal of Molecular Neuroscience, 2010)

Geostatistical analysis of biomarkers of genotoxicity in cattle, Bos taurus and Bos taurus × Bos indicus, sentinels near industrial facilities - Wesley Bissett; Roger Smith; L. Garry Adams; Robert Field; William Moyer; Tim Phillips; H. Morgan Scott; James A. Thompson (Ecotoxicology, 2009)

Identification of transposons, retroelements, and a gene family predominantly expressed in floral tissues in chromosome 3DS of the hexaploid wheat progenitor Aegilops tauschii - Ryan Whitford; Ute Baumann; Tim Sutton; Luke Gumaelius; Petra Wolters; Scott Tingey; Jason A. Able; Peter Langridge (Functional & Integrative Genomics, 2006)

Microcosm Evaluation of the Fate, Toxicity, and Risk to Aquatic Macrophytes from Perfluorooctanoic Acid (PFOA) - Mark L. Hanson; Jeff Small; Paul K. Sibley; Tim M. Boudreau; Richard A. Brain; Scott A. Mabury; Keith R. Solomon (Archives of Environmental Contamination and Toxicology, 2005)

CREB and the discovery of cognitive enhancers - Roderick Scott; Rusiko Bourtchuladze; Scott Gossweiler; Josh Dubnau; Tim Tully (Journal of Molecular Neuroscience, 2002)

wsp Gene Sequences from the Wolbachia of Filarial Nematodes - Chiara Bazzocchi; Wanwisa Jamnongluk; Scott L. O'Neill; Tim J.C. Anderson; Claudio Genchi; Claudio Bandi (Current Microbiology, 2000)

Improving the Evaluation of Conservation Programs - Devra G. Kleiman; Richard P. Reading; Brian J. Miller; Tim W. Clark; J. Michael Scott; John Robinson; Richard L. Wallace; Robert J. Cabin; Fred Felleman (Conservation Biology, 2000)
The evaluation of conservation programs is rare but increasingly important in improving their effectiveness. Regular evaluations of conservation programs and the implementation of recommendations resulting from such assessments are infrequent because of resistance by participants and lack of funding. Evaluations may be internal or external, depending on the purpose of the review and how broadly it is focused. We strongly recommend external peer review of long‐term complex conservation programs every 5 years, supported by more frequent (annual) internal reviews. Criteria for success must encompass both biological and social measures and include learning and the application of new knowledge to management. Evaluations must also go beyond monitoring to assess the value of the program. We emphasize the need to include the organization and function of a conservation program (the process) in any evaluation in addition to substantive criteria for success, which usually involve biological measures (numbers). A dysfunctional program organization and process can as effectively cripple a conservation effort as can a major biological catastrophe. We provide examples of different types of conservation program evaluations, including moderated workshops and case‐study analysis, and provide advice on the logistics and organization of the review, emphasizing the importance of the evaluation process itself to a successful outcome. One important aspect of an evaluation is having an individual with leadership ability and considerable expertise to organize the format and oversee the review process itself. Second, it is essential at the outset to ensure agreement among the program participants and the review committee on the goals and objectives of the conservation program, what is to be evaluated, and the criteria for defining success. Finally, the best evaluations are inclusive and involve all participants and stakeholders.

SKIN SWABBING FOR GENETIC ANALYSIS: APPLICATION TO DUSKY DOLPHINS ( LAGENORHYNCHUS OBSCURUS ) - April Dawn Harlin; Bernd Würsig; C. Scott Baker; Tim M. Markowitz (Marine Mammal Science, 1999)
A bstract Exfoliated skin was collected from bowriding dolphins with the use of a sterilized nylon scrub pad affixed to a wooden dowel. Initial tests of the effectiveness of the technique and dolphin behavioral responses were conducted on dusky dolphins off Kaikoura, New Zealand. During 14 sampling days, 128 contacts using this procedure were made with bowriding dolphins, of which 114 showed behavioral response. Responses during sampling were mild, with 11% of contacted individuals showing no visible response, and 66% of individuals which could be monitored for 30 sec after contact returning to bowride within 30 sec. Mean return time was 10 sec postcontact and did not vary significantly for groups of different sizes. Behavioral controls suggest that a proportion of responses could be explained by typical dolphin behavior in the presence of boats. Seventy‐eight percent of contacts resulted in successful collection of tissue samples. Sample time was three minutes on average. Size of group and behavioral state did not appear to influence sample time. Preliminary genetic analyses revealed that tissue collected by this technique was suitable for amplification and sequencing of mitochondrial DNA (mtDNA) via PCR. Comparisons of mtDNA control region sequences with those from known L. obscurus and other delphinid samples verified that this technique was robust against contamination from elements in sea water.

Identification of a modifier gene locus on chromosome 1p35-36 in familial adenomatous polyposis - Zuzana Dobbie; Karl Heinimann; D. Tim Bishop; Hansjakob Müller; R. J. Scott (Human Genetics, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)